Affect, Space and Memory in Ruinas (1866), a Novel by Rosalía de Castro - Costas López, Gisella (Madrygal. Revista de Estudios Gallegos, 2023)
Ruinas (1866) is a short novel written by Rosalía de Castro that proposes a dialectic between past and present through the image of ruins since it is also placed in a moment of transition that produces tensions while it creates new subjectivities. The aim of this analysis will be to take those main characters as spaces that contain a residual nature –in terms of Raymond Williams– that points towards the past as memory or latent presence of it and, at the same time, they point towards the future revealing in an allegorical way the contradictions of both models as well as their own mistrust towards them. The ruin’s trope enables then a Marxist interpretation, by means of the Affect Studies in dialogue with the ones related to the Spatial Turn, on the basis of the conception of the spectral body as a liminal and archaeological space that opens paths through memory and affect. That is to say, it reveals itself as a potentially destabilising place by positioning itself, because of its intermediality, as a point of resistance against the dominant system, supporting, additionally, cultural emergence.